Relationship between variety-seeking behaviour and need for closure - Tan, Jia Hui (2016)
This study was conducted to address the gap in existing literature in establishing the relationship between the need for closure (NFC) and variety-seeking behaviour, therefore facilitating a better understanding of the psychological mechanisms accounting for the differences in consumers’ purchasing behaviour. Previous research suggested environmental noise as one of the situational factors that affects the two posited construct. Therefore, this present study aims to validate the effect of NFC on variety-seeking behaviour during choice-task scenario, under different environmental noise manipulation. 40 undergraduates from Nanyang Technological University (NTU) were recruited for this study. Participants were required to complete a questionnaire that consisted of the need for closure scale (NFCS), choice-task scenario, and demographic survey. Results indicated a statistically insignificant negative correlation between the two constructs. Reasons that could account for the results are discussed and examined. Recommendations in regards to the current and future studies are also posited.